Artificial Intelligence in Water Conservation : A Meta-Analysis Study - Siddiqui, Aaliyah; Siddiqui, Mujahid; Kulkarni, Nirzar (Prabandhan: Indian Journal of Management, 2022)
In present times, the protection of the environment and the conservation of natural resources have emerged as the areas that need immediate attention for the survival and sustenance of the human population. One of the most prominent technological advancements is the surge of artificial intelligence (AI) in various fields. Research efforts to apply AI in water conservation (WC) have been made in multiple domains of study. This study involved a bibliographic analysis of such available documents in the combined field of AI and its application in WC. The analysis was performed using the two major databases of research literature: Web of Science and Scopus. Classification of the information was presented based on comprehensive research available, and then a screening was performed to find the open-access documents on the subject. Leading institutions and countries, most cited research works, leading authors, and the journals that contributed to this literature were presented through the analysis. We used VoS viewer and MS Power BI software for the keyword analysis and identification of contributing countries. The analysis of documents of the past two decades from 2000 – 2020 is presented in the study.